The level of teacher creativity to overcome limitations of infrastructure and facilities in the learning process of PJOK in SMP Sub-district Sukoharjo, Sukoharjo Regency, 2020 - Pingky Meilina Cahayanti; Waluyo Waluyo; Ahmad Septiandika Adirahma (PHEDHERAL, 2020)
The problem that occurs in this study is that there are still many PJOK infrastructure and facilities that have not met as they should be, not comparable to the number of students, there are some teachers who are less creative in making tool modifications, and many teachers are still waiting for assistance from PJOK infrastructure and facilities from the school. This study aims to determine the level of teacher creativity to overcome the limitations of infrastructure in the learning process of PJOK in junior high schools in Sukoharjo District, Sukoharjo Regency. This research uses a quantitative descriptive research approach. The method used in this research is a survey method with data collection techniques using a questionnaire as primary data, as well as observation, and documentation as secondary data. The population of this study were all PJOK teachers in junior high schools in Sukoharjo District, Sukoharjo Regency, totaling 23 teachers. The data analysis used was a descriptive analysis of the percentage. The results showed that the creativity of sports and health physical education teachers in responding to the limitations of physical education facilities and infrastructure in junior high schools in Sukoharjo District, Sukoharjo Regency as a whole was categorized as 1 teacher (4%) in the very high category, 6 teachers (26.09%) in high category, 10 teachers (43.48%) in the medium category, 4 teachers (17.39%) in the low category, and 2 teachers (8.70%) in the very low category. It can be concluded that the creativity of sports and health physical education teachers in responding to the limitations of physical education facilities and infrastructure in junior high schools in Sukoharjo District, Sukoharjo Regency is in the medium category (43.48%).